(untitled) (Contemporary Journal of Social Science Review, 2025)
Climate change poses significant and widespread threats to girls’ education globally. It impacts the continuity, quality, and accessibility of education. This research examines the effects of climate-induced disasters, including floods, droughts, and heat waves, in four districts of Balochistan. The study employed a mixed-methods approach to gather both qualitative and quantitative data using questionnaires, interviews, and focus group discussions. A sample of 330 participants, comprising female students, teachers, school administrators, parents, community members, and NGO representatives, was selected using simple random and purposive sampling techniques. The primary indicators of attendance rate, dropout rate, learning outcomes, teacher availability, infrastructure damage, and delays in school reopening were examined to evaluate the effects of climate change on education. The findings of the study reveal that climatic disasters severely affected school attendance and continuity of education, as evidenced by a 35% drop in attendance in flood-affected areas. The dropout rate among girls significantly increased due to displacement, financial constraints, and safety concerns. Moreover, the quality of education also decreased due to teachers’ absenteeism and deteriorated classroom conditions, leading to a 20% drop in average student performance. Access to education was further restricted due to road destruction and school closure for an extended period, affecting enrollment and attendance after climate disasters. To establish a resilient learning system in Baochistan, the study recommends constructing flood and drought-resistant school buildings, incorporating climate change education into national curricula, and implementing community-based learning programs wherein educated individuals assist students during climate emergencies that disrupt formal schooling. Policy reforms, increased government funding, and improved coordination between educational and disaster management authorities can establish a sustainable learning system in climate-affected regions. By implementing these initiatives, Balochistan can build a resilient education system to ensure the future of girls’ education despite severe ongoing climatic challenges.